Unchopping a Tree Reconciliation in the Aftermath of Political Violence - Verdeja, Ernesto (Temple University Press, 2009)
Political violence does not end with the last death. A common feature of mass murder has been the attempt to destroy any memory of victims, with the aim of erasing them from history. Perpetrators seek not only to eliminate a perceived threat but also to eradicate any possibility of alternate, competing social and national histories. In this timely and important book, Ernesto Verdeja develops a critical justification for political reconciliation. He asks the questions "What is the balance between punishment and forgiveness?" and "What are the stakes in reconciling?"Developing a normative theory of reconciliation that differs from prevailing approaches, Verdeja outlines a concept that emphasizes the importance of shared notions of moral respect and tolerance among adversaries in transitional societies. Drawing from reconciliation efforts around the world-and interviews with people involved in such endeavors-Verdeja debates how best to envision reconciliation while taking into account the very significant practical obstacles that confront such efforts.Unchopping a Tree addresses the core concept of respect at four different social levels-political, institutional, civil society, and interpersonal-to explain the promise and challenges of securing reconciliation and broader social regeneration.